In vitro antifungal activity of Peltophorum dubium (Spreg.) Taub. extracts against Aspergillus flavus. - Di Ciaccio, Lucía Soledad (2020)
Aspergillus flavus is a filamentous, saprophytic fungus, whose colonization occurs mainly in cereal grains and oilseeds once arvested. Under certain conditions, it could produce mycotoxins called aflatoxins, known as powerful human liver carcinogens. The aim of the present study was to describe the antifungal activity of extracts of Peltophorum dubium, a species from northern Argentina (Oriental Chaco), against A. flavus. The antifungal activities of di erent collection sites are reported. The extracts exhibited a minimum inhibitory concentration of 125 g/mL, and the di erences between the treatments and the inoculum control were 11 mm of P. dubium A and 10 mm of P. dubium F in colony growth. Moreover, hyphae treated with the extracts stained blue with Evans blue showed alterations in the membrane and/or cell wall, allowing the dye income. Bio-guided fractionation, High Performance Liquid Chromatography diode array ultraviolet/visible (HPLC UV/VIS DAD), and Ultra-High Performance Liquid Chromatography Electrospray Ionization Mass Spectrometry (UPLC ESI-MS) analyses were conducted to characterize the extracts and their active fractions. The HPLC UV/VIS DAD analysis allowed the determination of the presence of flavonoids (flavonols and flavones), coumarins, terpenes, and steroids. UPLC ESI/MS analysis of active fractions revealed the presence of Kaempferol, Apigenin, Naringenin, Chrysin and aidzein.